The Predictive Role of Protective Models and Controls among Family members, Peers, Classmates, and Neighbors in Deviant Behavior of Adolescents - Mojtaba Habibi Asgarabad; Nikzad Ghanbari; Moloud Sivandian; Haniyeh Mehdizadeh Hanjani (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Family members, peers, classmates and neighbors play a crucial role in determining juvenile deviant behavior. Therefore, the purpose of this study was determining the predictive role of protective models and controls among family members, peers, classmates, and neighbors in deviant behavior of adolescents. Materials and Methods: This study was of cross-sectional correlational design. Participants included 1847 female and male high school students of the 20 districts of Tehran in the academic year 2013-2014. Participants were selected via multi-stage cluster sampling. Data were collected via socio-mental protective and risk factors and behaviors scale. Data were analyzed using multiple regression analysis, stepwise method by SPSS-24 statistical software. Results: The participants were 946 (51.2%) girl and 901 (8.48%) boy and the mean (SD) age of participants was 16 (1.2). Protective models and controls of peers (P<0.001), family members (P<0.001), classmates (P<0.001), and neighbors strongly predict deviant behavior in adolescents. In addition, there was no significant correlation between models protection of family and deviant behavior. Conclusion: The study showed stronger role of peers, family members, classmates, and neighbors predict less deviant behavior in adolescents. DOI: http://doi.org/10.22037/ch.v6i1.19892